64 Screening of patients with a family history of premature coronary artery disease. (5th October 2017) - Ranganathan, D; O'Carroll-Loliat, C; Kinsella, R; Reynolds, A; Ward, D
Abstract : Introduction: Family history of premature coronary artery disease (pCAD) increases CAD risk in first-degree family members by 2 to 3-times by increasing susceptibility to atherosclerosis development. Screening and appropriate risk management could result in avoidance of myocardial infarction or sudden cardiac death. Aim: To assess for evidence of atherosclerotic coronary disease, through computed tomography coronary angiography (CTCA), in patients with a family history of pCAD (FHx +), to guide appropriate management and follow up. Method: This was a single-centre, cross sectional study conducted in the Cardiac Risk in Younger Persons (CRYP) centre between the years 2009–2016. A total of 547 patients were assessed clinically, including blood investigations. Individuals were considered for CTCA when they were 10 years younger than the earliest cardiac event in the family. Results: 230 of the cohort (42%) had a total cholesterol level >5 mmol/L. 33 of these individuals have had CTCA to date. 16 (48%) who underwent CTCA had evidence of atherosclerosis, with 4 (12%) requiring intervention either by means of Primary Coronary Intervention or Coronary Artery Bypass. 12 individuals (36%) had evidence of non-obstructive coronary plaques and commenced on secondary prevention with aspirin and statin. The remaining 52% have been reassured and managed conservatively with lifestyle advice and plans to reassess in 5 years. Subanalysis of CTCA results comparing patients with high total cholesterol (> 5 mmol/L) levels with pCAD (FHx+) and patients without a family history of pCAD (FHx-) showed 50% of FHx+ patients showed plaque requiring intervention compared to 16.6% (1 out of 6) in FHx-. Conclusion: Our study demonstrated that the risk of having a family history of pCAD increased healthy, asymptomatic individuals risk of CAD, with almost 2-fold risk increase. Although screening in asymptomatic patients is controversial, given the socioeconomic impact from the consequence of CAD in this group of patients; it potentially allows early detection and alteration of the natural history. In addition, over 50% of our cohort with a positive family history and elevated cholesterol showed no evidence of plaque formation, and can potentially defer pharmacological therapy pending reassessment. A lack of current guidelines on age to commence formal CV risk assessment and risk management, results in ad hoc practices. Studies of families with genetically proven FH confirm that not all affected individuals develop premature atherosclerosis, and therefore do not require early aggressive pharmacological intervention. CTCA is emerging as a promising modality to improve screening in this population given the low radiation dose with ECG-gated CTCA, and should be considered even in low-risk patients with a family history of pCAD.